Bentuk dan Fungsi Ragam Hias Bunga Melati pada Arsitektur Candi - Fatimah, Dina; Luthfiah, Vinie (Waca Cipta Ruang, 2019)
Decorative or ornamentation aims to fill the void in the surface area of ​​an object. The decoration is one of the identities inherent in Indonesian cultural artifacts (one of which is in the temple). There are various types of decoration that exist in Indonesia, is a result of the diversity of races, religions and cultures. The decoration on the temple with non-story relief is divided into four, namely the geometric decoration, fauna, flora in which there are forms of vines, roses, jasmine and sun, as well as various decorative ornaments. With a qualitative descriptive method, the author made observations, discovered the role, shape and function of jasmine ornamental variations in the temple building. The decoration on the temple with the shape of jasmine is combined with the geometric decoration. Jasmine decoration is a non-structural decoration, symbolizing purity found in the feet. Keywords: ornamental variety, temple, jasmine flower